Changing Norms About Gender Inequality In Education : Evidence From Bangladesh - Blunch, Niels-Hugo (The World Bank, 2007)
Using a recent household survey for two cohorts of married women, this paper examines norms about gender equality in education for children and adults. Among the main findings are that gender education gap norms have changed: younger generations of women are more positive about female vs. male education, both as pertaining to child and adult education outcomes. Perhaps the strongest result is that Bangladeshi women are more likely to espouse attitudes of gender equality in education for their children and less so about gender equality among spouses. It is also easier to explain norms regarding children's education and more difficult to explain norms about equality in marriages. The authors believe that question on relative education of boys and girls captures the value of education per se, while the question on educational equality in marriage captures the norms regarding marriage and the relative worth of husbands and wives. The effect of education in determining norms is significant though complex, and spans own and spousal education, as well as that of older females in the household. This indicates sharing of education norms effects or externalities arising from spousal education in the production of gender education gap norms within marriage as well as arising from the presence of older educated females in the household. Lastly, the authors also find associations between gender education gap norms and household poverty, information processing and religion, though the evidence here is more mixed